2020
DOI: 10.1021/acsami.0c05077
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Dry Adhesion of Polymeric Micropatterns by Electric Fields

Abstract: Micropatterned dry adhesives rely mainly on van der Waals interactions. In this paper, we explore the adhesion strength increase that can be achieved by superimposing an electrostatic field through interdigitated subsurface electrodes. Micropatterns were produced by replica molding in silicone. The adhesion forces were characterized systematically by means of experiments and numerical modeling. The force increased with the square of the applied voltage for electric fields up to 800 V. For larger fields, a less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Reproduced with permission. [ 175 ] Copyright 2020, ACS [https://pubs.acs.org/doi/10.1021/acsami.0c05077, further permissions related to the material excerpted should be directed to the ACS].…”
Section: Hybrid Ea Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…Reproduced with permission. [ 175 ] Copyright 2020, ACS [https://pubs.acs.org/doi/10.1021/acsami.0c05077, further permissions related to the material excerpted should be directed to the ACS].…”
Section: Hybrid Ea Technologymentioning
confidence: 99%
“…Recently, Vaishali et al fabricated a simple design of silicone micropillars with IDT electrode layer beneath demonstrating a coupled gecko EA device, as displayed in Figure 11j. [ 175 ] The authors also examined a simulation model which tested out the effects of various parameters like dielectric thickness, the conductivity of medium and elastomer, dielectric constants, electrode geometry, and so on. The hybrid device produced twice as large adhesion as compared to standalone systems and the simulation parameters largely matched the experimental investigations.…”
Section: Hybrid Ea Technologymentioning
confidence: 99%
“…As a consequence, the tangential adhesive capacity of the electrostatic adhesion was increased by 4 times, and the tangential adhesive capacity of the hybrid adhesive component on the surface of different materials was increased by 2 times [128]. Recently, the coplanar comb electrodes were also embedded into the vertical cylindrical microfiber array [129]. Experimental confirmed that the addition of electrostatic adhesion not only improves the normal adhesive capacity of the hybrid component, but also reduces its need for net preload.…”
Section: The Gecko-like Dry Adhesive Surfaces With the Adaptive Characteristic For Rough Surfacementioning
confidence: 99%
“…[ 6–11 ] Biologically inspired structures of smart and switchable adhesives have been actively developed to achieve reversibility by applying external stimuli, such as temperature, light, voltage, and mechanical load. [ 12–22 ] Despite advances in artificial adhesives, strategies of effective switches between strong adhesion for object pickup and weak adhesion for object placement are still rare.…”
Section: Introductionmentioning
confidence: 99%